Awareness of Personal Data Protection Law in concern to literacy - Sadeli, Annisa Fajriyati; Irawati, Indira (Universitas Padjadjaran, 2023)
Understanding privacy literacy can help everyone treat their personal data shared on online platforms. Data protection starts from the idea that individuals have the right to information about themselves. There must be efforts to prevent misuse; hence, it makes digital literacy important. This research aimed to measure students' understanding of the importance of protecting personal data in the PDP Law based on the categories of knowledge, attitudes, and behavior. The research used quantitative methods with an analytical survey approach. Data analysis techniques used the Analytical Hierarchy Process (AHP). The population was 75 undergraduate and postgraduate students in West Java. The final score showed the number 81. Research results showed that the knowledge dimension scored 82, or a good level. It explained that most respondents understood data privacy protection laws. The attitude dimension had a score of 83, classified as good. Respondents were expected to stay informed about information protection and data privacy. The behavioral dimension was lower than the other dimensions, namely 77 or classified as an average level. In conclusion, the awareness level of the Data Privacy Protection Law based on the areas and dimensions that have been taken into account is at a good level, although it still needs improvement in terms of habits or behavior.